BaSc2(HPO3)4(H2O)2: a new nonlinear optical phosphite exhibiting a 3D {[Sc2(HPO3)4]2−}∞ anionic framework and phase-matchable SHG effect. Issue 20 (8th September 2022) - Tang, Ru-Ling; Liu, Gang-Xiang; Yao, Wen-Dong; Zhang, Li-Nan; Liu, Wenlong; Guo, Sheng-Ping
Abstract : The first barium scandium phosphite, BaSc2 (HPO3 )4 (H2 O)2, has been systematically studied. It exhibits a 3D [Sc2 (HPO3 )4 ] 2− anion framework with an SHG effect (0.94 × KDP) and phase-matching behaviour. Abstract : Phosphite materials have aroused wide attention due to their diverse open frameworks and promising magnetic and optical performances. Here, the first barium scandium phosphite, BaSc2 (HPO3 )4 (H2 O)2, was obtained via a facile hydrothermal route. BaSc2 (HPO3 )4 (H2 O)2 crystallizes in the polar space group Pn and exhibits a 3D {[Sc2 (HPO3 )4 ] 2− }∞ anion framework constructed by distorted ScO6 octahedra and HPO3 2− anion groups. BaSc2 (HPO3 )4 (H2 O)2 can exhibit a phase-matchable SHG response of about 0.94 × KH2 PO4 at 1064 nm, and a moderate birefringence (0.036@1064 nm) to satisfy the phase-matchable behavior requirement. Deep investigation of its structure–property relationship based on theoretical calculations has also been presented in this work.